The informant! [videorecording (DVD)] - Soderbergh, Steven, 1963-; Damon, Matt; Lynskey, Melanie; Bakula, Scott; McHale, Joel, 1971-; Hamlisch, Marvin (Distributed by Warner Home Video, 2010)
The U.S. government decides to go after an agri-business giant with a price-fixing accusation based on the evidence submitted by their star witness, vice president turned informant Mark Whitacre. The FBI needs evidence, so Whitacre eagerly agrees to wear a wire and carry a hidden tape recorder in his briefcase, imagining himself as a kind of de facto secret agent.